Node Isolation Attack on OLSR ,Reputation Relied Mitigation - Dr.B.Barani sundaram, Mr.Tucha kedir, Mr.Tesfaye tadele sorsa, Mr.Rabira geleta,Dr.Nune srinivas, Adola haile genale (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Mobile Ad Hoc Networking (MANET) is an excellent Technology which is taking its importance because of the wide range of wireless portable devices exploiting this facility. Mobile ad hoc networks are highly vulnerable to attacks due to the open medium, dynamically changing network topology, cooperative algorithms, lack of centralized monitoring and management point. The traditional way of protecting networks with firewalls and encryption software is no longer sufficient and effective for handling the threats associated. Now, a day many applications are constructed with help of proactive routing protocol in MANETs using OLSR protocol. These applications are useful for disaster relief, emergency operations, and military service and so on.